2011
DOI: 10.1042/bst0390989
|View full text |Cite
|
Sign up to set email alerts
|

Old and new findings on lipopolysaccharide-binding protein: a soluble pattern-recognition molecule

Abstract: LBP [LPS (lipopolysaccharide)-binding protein] was discovered approximately 25 years ago. Since then, substantial progress has been made towards our understanding of its function in health and disease. Furthermore, the discovery of a large protein family sharing functional and structural attributes has helped in our knowledge. Still, key questions are unresolved, and here an overview on the old and new findings on LBP is given. LBP is an acute-phase protein of the liver, but is also synthesized in other cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 95 publications
3
116
1
3
Order By: Relevance
“…Moreover, we found that the LBP-MetS association was more pronounced in normal-weight participants than in overweight and obese individuals. Since its discovery in the 1980s, LBP has been considered a key protein in mediating LPS-triggered innate immunity in a CD14-and TLR4-dependent manner [7,20]. As a surrogate marker of LPS, circulating LBP concentration was shown to be positively associated with prevalence of MetS in our previous overweight/obese case-control analysis [9].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, we found that the LBP-MetS association was more pronounced in normal-weight participants than in overweight and obese individuals. Since its discovery in the 1980s, LBP has been considered a key protein in mediating LPS-triggered innate immunity in a CD14-and TLR4-dependent manner [7,20]. As a surrogate marker of LPS, circulating LBP concentration was shown to be positively associated with prevalence of MetS in our previous overweight/obese case-control analysis [9].…”
Section: Discussionmentioning
confidence: 69%
“…However, owing to its short half-life and interference in the blood, it is difficult to measure circulating LPS in large-scale population-based studies [6]. By contrast, lipopolysaccharide binding protein (LBP), which is mainly synthesised in the liver, could specifically bind to and monomerise exogenous LPS, thereafter enabling the endotoxin to be recognised by Toll-like receptor 4 (TLR4) and cluster of differentiation 14 (CD14), which are responsible for consequent innate immunity [7]. Therefore, circulating LBP levels, with a relatively long half-life, have been used as a variable to assess endotoxaemia status and its immune responses [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid A interacts with almost all host cells but has been investigated mainly in relation to monocytes and macrophages (184). LPS-binding protein (LBP), a soluble acute-phase protein, binds LPS and shuttles it to the membrane-bound CD-14 receptor (185). The CD-14 receptor facilitates transfer to the TLR-4/MD-2 receptor complex.…”
Section: Fig 6 O-antigen Lps Biosynthesis and Lps Assembly And Transpmentioning
confidence: 99%
“…In CD14-positive cells (e.g., macrophages), TLR4 is internalized in endosomes where it dissociates from MyD88 and interacts with TRIF to activate IRF3 (7,12). LBP belongs to a LBP/bactericidal/permeability-increasing protein/palate, lung and nasal epithelial clone protein superfamily and is produced primarily in liver and epithelial cells of the lungs and gastrointestinal tract as an acute phase serum glycoprotein (25). The family members constitute physical barriers against bacterial infection in innate immunity (25,26).…”
Section: Introductionmentioning
confidence: 99%